ヒガシ オングル トウ ミズクミザワ ノ リュウキ テイセン ノ チケイ ト シュウヒョウガ チケイ ニホン ナンキョク カンソクタイ ノ ホウコク - 藤原, 健蔵; フジワラ, ケンゾウ; FUJIWARA, Kenzo (国立極地研究所, 1973)
P(論文) Based on the investigation of micro-reliefs and deposits of the Mizukumi Zawa (Valley), which is a small glacial trough near Syowa Station, geomorphic evolution after recession of ice sheet was studied. The valley floor in the investigated area was divided into five raised beaches and gentle slopes above them. The raised beaches are referred to as surfaces I (14.0-11.5m. a. s. l.), II (10.0-9.5m.), III (7.0-6.0m.), IV (4.5-3.0m.) and V (below 2.0m.), surface I being the oldest. The molluscan shells contained in the deposits of surfaces I gave a ^<14>C date a little older than 30,000yr. B. P. and the surface V date 3,000-6,000yr. B. P. (YOSHIDA, 1970). Therefore, it seems that surfaces I and V were formed owing to the marine transgressions during the interstadial oscillation that preceded the Late Wurm glaciation and during the postglacial age, respectively. Surface II is a product of the marine regression that followed immediately after the interstadial oscillation. It is impossible to date definitely surfaces III and IV, which are composed of thick coarse materials, because the radiocarbon ages of shells on the surfaces range widely from 20,000 to 31,000yr. B. P. As a rule periglacial processes in this area are slight, on account of the summer weather with relatively few freeze-thaw cycles and low precipitation. The gentle slopes, constituting the upper part of valley floor, are the result of the repeated freeze-thaw which shatters the bedrock and of the solifluction which removes the debris. The upper slope at the foot of valley walls is the steepest, and is the source of the slope debris. The middle and lower slopes have smooth surfaces with low angles and are covered with fine debris of freeze-thaw. And, the north-facing slopes are developed better than the south-facing ones. The processes that account for such characters of these gentle slopes are discussed. Other landforms, such as cryoturbation steps, patterned ground and rock shattering, are also described. departmental bulletin paper